Sedimentologic and palaeoenvironmental evolution of the Mamfe Cretaceous Basin (SW Cameroon): Evidence from lithofacies analysis, tectonics and evaporite minerals suite. (January 2019) - Eyong, John Takem; Gabriel, Ngueutchoua; Moïse, Bessong; Hell, Victor Joseph; Eric, Bokanda Ekoko; Wignall, Paul; Best, Jim
Abstract: Lithofacies analysis, optical microscopic and X-ray diffraction approaches were employed to investigate basin-fill configuration and palaeodepositional environments of the Mamfe Cretaceous Basin in SW Cameroon. The asymmetric basin-fill comprises six lithofacies associations whose vertical architectures are influenced by early syn-rift, mid syn-rift and post-rift tectonics episodes coupled with climatic and sedimentological factors: (1) basal conglomerates-breccias-sandstones (association A1) is interpreted as proximal alluvial fans and fluvial channel deposits; (2) thinly bedded mixed siliceous and carbonate sandstones-siltstones-shales (association A2) with ripple marks and desiccation cracks is interpreted as floodplain deposits; (3) sandstones with pebble lags-, scour-filled heterolithic facies-shales-palaeosols (facies association A3) characterises fluvial channel deposits with wave-dominated bars or dunes deposited in marginal fluvio-deltaic environments; (4) organic-rich micritic, oolitic and pelletoidal shales-siltstones-limestones-sandstones (association A4) reflects open lake pro-deltaic deposits; (5) prograding cross-bedded sandstones-shales-pyroclastics-coals-palaeosols (association A5) reflects subaqueous fluvio-lacustrine deltaic and swamp deposits; (6) pebble sandstones and sandy-mudstones (association A5) is interpreted as fluvial channel deposits at the terminal stage of the life cycle of the basin. Evidence from evaporite minerals suite (halite, dolomite, gypsum and polyhalite) associated with metal sulphides suggests deposition in mixed oxic and sulphur reducing anoxic hypersaline environments subjected to evaporation and reflux under arid climate. Dolomite-rich evaporite-host lithofacies (oolitic, pelletoidal and algal mats) with low faunal diversity in ostracods, algae, fish bones, gastropods and conchostracans indicate stressed hypersaline settings common in fluvio-lacustrine and lagoon environments. Humid and warm palaeoclimate regimes with cyclic sub-aerial exposure prevailed from Early to Middle Cretaceous. A pronounced arid climate with restricted drainage and low detrital to carbonate sediment fluxes into a confined fluvio-lacustrine lake prevailed during Aptian-Albian. The deposition of evaporite and clay (chlorite/chamosite-illite-muscovite) mineral suites, palaeosols, caliches, hardgrounds and desiccation cracks are thumbprint vestiges of arid climate. Highlights: Lithofacies of the MCB are deposited in alluvial and fluvio-lacustrine environments. The asymmetric basin-fill configuration is linked to three tectonic episodes. Evaporite minerals of the basin include halite, dolomite, gypsum and polyhalite. Evaporite-host rocks comprise oolitic, peloidal, algal mat and sandstone facies. Arid and stressed hyper-saline environments prevailed during Early Cretaceous.